Detection of HPV DNA and immunohistochemical expression of cell cycle proteins in oral carcinoma in a population of brazilian patients - Rosilene Calazans Soares; Márcio Campos Oliveira; Lélia Batista de Souza; Antônio de Lisboa Lopes Costa; Leão Pereira Pinto (University of São Paulo, 2008)
This study investigated the presence of human papillomavirus (HPV) DNA and viral types in 33 cases of oral squamous cells carcinoma (OSCC) and compared the immunohistochemical expression of the cell-cycle markers p21 and pRb between cases of the disease with and without HPV. DNA was extracted from paraffin-embedded tissue and amplified by PCR for the detection of HPV DNA. Viral typing was performed by dot blot hybridization. Immunohistochemistry was performed by the streptavidinbiotin technique. HPV DNA was detected in 11 (33.33%) of the 33 cases. The prevalent viral type was HPV 18 (81.81%). A significant association was observed between the presence of HPV and immunohistochemical expression of pRb, but not between p21 expression and the presence of the virus. The low frequency of detection of HPV DNA in OSCC suggests a possible participation of the virus in the development and progression of only a subgroup of these tumors.